FRI0378 Cardiac involvement in undifferentiated connective tissue disease at risk for systemic sclerosis. a tissue doppler imaging study. (15th June 2017) - Riccardi, A; D'Alto, M; Argiento, P; Romeo, E; Stefano, I Di; Fasano, S; Iacono, A Mattera; D'Andrea, A; Sanduzzi, A; Bocchino, M; Docimo, L; Tolone, S; et al.
Abstract : Background: Undifferentiated connective tissue disease at risk for Systemic Sclerosis (UCTD-risk-SSc), previously referred to as very early SSc, is a condition characterized by Raynaud's phenomenon (RP) with SSc marker autoantibodies and/or typical capillaroscopic findings and unsatisfying classification criteria for the disease (1). UCTD-risk- SSc patients have been reported to present, in about 40% of the cases, a preclinical vascular internal organ disease as detected by a diffusing lung capacity for CO <80% of the predicted value (lung involvement) and/or a low esophageal sphincter pressure <15 mmHg (oesophageal involvement) and/or a mitral E/A ratio <1 (heart involvement) (2, 3). Objectives: Aim of the present study was to assess the prevalence of right (RV) or left ventricle (LV) systolic and/or diastolic dysfunction by standard echocardiography and tissue Doppler imaging (TDI). Methods: Thirty patients with UCTD-risk-SSc (28 female, aged 47±13 years, range 21–70) and 30 age- and sex-matched controls underwent cardiac assessment by standard echocardiography and TDI. Results: UCTD-risk-SSc patients and controls did not show any difference at standard echocardiographic evaluation. In particular, an inverted E/A ratio was pointed out in 10/30 patients and 7/30 controls (p=ns). TDI showed a mild impairment of LV and RV diastolic (Em 15±4 vs 19±5, p<0.0001;E/Em 6.1±1.7 vs 4.8±1.2, p=0.001; Et 14±3 vs 16±2, p=0.02; Et /At 0.9±0.4 vs 1.3±0.3, p<0.002; increased pulmonary artery wedge pressure 9±2 vs 8±1, p=0.001)and systolic function (Sm 13±3 vs 15±2 cm/sec, p<0.0003; St 14±2 vs 16±3 cm/sec, p<0.0001) in UCTD- risk-SSc patients in comparison to controls. Conclusions: Our study shows that UCTD-risk-SSc patients present a previously unrecognized, mild biventricular systolic and diastolic dysfunction as compared to controls. The pathophysiologic meaning (i.e.intramyocardial artery disease and/or patchy fibrosis) as well the predictive value of developing overt SScin the short time await to be elucidated. Disclosure of Interest: None declared